Nuevas negociaciones entre el realismo y lo insólito en algunos cuentos de Federico Falco (Revista de Crítica Literaria Latinoamericana, 2025)
Federico Falco’s (Córdoba, Argentina, 1977) narrative project cannot be considered as fantastic, although it sometimes uses the resources of the fantastic, especially in relation to the place-landscape-subject coordinates. The wasted borders that his stories suggest move in an intergenre that transgress the limits of the possible without stridency. I think of the unusual in this narrative not as a macro-genre but as a fluid collaboration between non-mimetic genres that generates the effect of an “augmented reality” that dares realistic representation. I will work on some stories from La hora de los monos (2010), 222 patitos (2004), and Un cementerio perfecto (2016).
Keywords: The unusual; Landscape; Place; Argentine narrative